(3GdCMLGQs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI (B: (3bGd eaSQ gPG GdcJGH(B: (3Ef CQSWGWGdjS hUa ai cJGHg GdPi fYJ ajg GdMLGQ s
(3BNQgG (B:s
(3hEf NQL CNVQ de jYGdL UGMHg eQjVkG EdG HQF HEPf Gddg Je cJGH CQSWGWGdjS ai Yde GdCMLGQ hGdMeOddg s
(3HBNQgG UaMI HYfhGf (B: (3Gdbhd ai GdNQR PcQ ajgG fYhJ GdNQR hNhGUgGs
(3gPG GdcJGH ef GdJQLeGJ GdbOjeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B4 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
Keywords: (3GdcjejGA h GdWHjYjGJs